2013
DOI: 10.4028/www.scientific.net/amm.341-342.1299
|View full text |Cite
|
Sign up to set email alerts
|

Review on Application of Hybrid Energy Storage Based on Ultracapacitor

Abstract: Characteristics of ultracapacitor and classic model have been introduced in this paper. Due to its superior performance, ultracapacitor is used for hybrid energy storage system with lead-acid battery. The performance and potential application of hybrid energy storage system have been elaborated, which make some contribution to the promotion and application of energy storage technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For comparison with the several energy-storage technologies, the energy density and power density for the linear/nonlinear dielectric films and the commercial electrostatic capacitors, electrochemical supercapacitors, Li-ion batteries, and fuel cells are summarized in Figure . , The Si:HfO 2 AFE thin films exhibit a high power density (∼10 9 -10 10 W/kg) as compared with the supercapacitors, batteries, and fuel cells. However, the energy-storage density of Si:HfO 2 AFE thin films (∼2.1 Wh/kg) is comparable to the supercapacitors but smaller than those of the Li-ion batteries and fuel cells.…”
Section: Energy-storage Properties Of Hfo2-based Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison with the several energy-storage technologies, the energy density and power density for the linear/nonlinear dielectric films and the commercial electrostatic capacitors, electrochemical supercapacitors, Li-ion batteries, and fuel cells are summarized in Figure . , The Si:HfO 2 AFE thin films exhibit a high power density (∼10 9 -10 10 W/kg) as compared with the supercapacitors, batteries, and fuel cells. However, the energy-storage density of Si:HfO 2 AFE thin films (∼2.1 Wh/kg) is comparable to the supercapacitors but smaller than those of the Li-ion batteries and fuel cells.…”
Section: Energy-storage Properties Of Hfo2-based Thin Filmsmentioning
confidence: 99%
“…Energy density and power density of the linear and nonlinear dielectric capacitors are compared with those of the conventional electrostatic capacitors, electrochemical capacitors (supercapacitors), Li-ion batteries, and fuel cells. Reproduced with permission from ref . Copyright 2017, AIP Publishing.…”
Section: Energy-storage Properties Of Hfo2-based Thin Filmsmentioning
confidence: 99%
“…With the increase of power requirement in modern societies, the energy storage systems are becoming crucial for energy conversion including electrochemical capacitors, Li-ion batteries, fuel DOI: 10.1002/advs.202300792 cells, and electrostatic capacitors. [1][2][3][4] Among various energy storage systems, electrostatic solid state supercapacitors of polarizable materials have received increasing interest due to their advantages of high energy density with larger power density, and are quite promising for rapid-chargedischarge applications. [5,6] Antiferroelectric dielectrics are ideal selections based on their high maximum polarization (P m ) and low residual polarization (P r ).…”
Section: Introductionmentioning
confidence: 99%
“…The direct battery-supercapacitor combination for the engine cranking in automotive engines resulted in the increased total number of cranking by the battery [11] and it is also reported that a 15-litre diesel-engine was attempted to start with open circuit voltage of around 11 V with 40% SOC of the battery but could not start the engine, but 64 KJ electrochemical capacitor when charged at 11 V from the same battery system, it started the engine four times at 0 o C [12]. In power system also, the supercapacitors play crucial role for power quality, capacity enhancement of the micro-grid, and motor starting to reduce cost of starting devices [13], [14]. Even, in the case of large induction motors, starting and fluctuating loads causes serious effect of instability on the diesel-generator operation due to wide frequency variations [15].…”
Section: Introductionmentioning
confidence: 99%